Sistem Informasi e-Verifikasi Keuangan Pada Instansi Pemerintah Daerah - Sabto Kironowati; Tazkiyah Herdi (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2019)
The development of e-government has become the focus of regional government nowdays. The move is meant to push the acceleration of an efficient and transparent governance particularly in public service improvement. One of the indicators of the success of transparency in financial management of local government is "unqualified opinion" by the Supreme Audit Agency (BPK). However, there are still some problems in verification stage such as error in data input, wrong budget usage and document of expendirure report are not in line with the prevailing laws and regulations. In the previous researches it was stated that e-government has emerged as a solution for the financial management, but yet to cover the verification process. The effort to solve the problem is by creating an IT-based e-verification information system using prototype development system method for the management of procurement verification of local government. The system is developed to verify the procurement of goods and services as stated in the procurement list (PaBJ) of budget implementation (DPA) as the referrence for the treasury department for budget disbursement